A: Length of focal chord of a parabola \[{{y}^{2}}=8x\] making an angle of ${{60}^{\circ }}$ with x-axis is $\dfrac{32}{3}$ .
R: Length of focal chord of parabola ${{y}^{2}}=4ax$ making an angle $\alpha $ with x-axis is $4a\cos e{{c}^{2}}\left( \alpha \right)$ .
Answer
Verified
465.3k+ views
Hint: Take the coordinate of focal chord A and B as $\left( a{{t}^{2}},2at \right)$ parametric form. Find the length of focal chord AB. Take slope as equal to t and thus substitute and prove $4a{{\cos }^{2}}\alpha $. Put $\alpha ={{60}^{\circ }}$ and get the value of a, to get the value of $\dfrac{32}{3}$.
Complete step by step answer:
We have been given the equation of parabola as \[{{y}^{2}}=8x\] .
The length of the focal chord, ${{t}_{1}}{{t}_{2}}=-1$ i.e. ${{t}_{2}}=\dfrac{-1}{{{t}_{1}}}$ ,
Hence, if A and B are the coordinate of the point on the parabola then. We can take their coordinate as,
$A\left( at_{1}^{2},2a{{t}_{1}} \right)$ and $B\left( at_{2}^{2},2a{{t}_{2}} \right)$ .
But we found out that ${{t}_{2}}=\dfrac{-1}{{{t}_{1}}}$ .
$\therefore $ coordinate of B changes to, \[B\equiv \left( a{{\left( \dfrac{-1}{{{t}_{1}}} \right)}^{2}},2a\left( \dfrac{-1}{{{t}_{1}}} \right) \right)\equiv \left( \dfrac{a}{t_{1}^{2}},\dfrac{-2a}{{{t}_{1}}} \right)\].
Let’s assume ${{t}_{1}}=\dfrac{-1}{{{t}_{2}}}=t$.
Thus, we can write the coordinate as \[A\left( a{{t}^{2}},2at \right)\] and $B\left( \dfrac{a}{{{t}^{2}}},\dfrac{-2a}{t} \right)$ .
So, here $\left( {{x}_{1}},{{y}_{1}} \right)=\left( \dfrac{a}{{{t}^{2}}},\dfrac{-2a}{t} \right)$, $\left( {{x}_{2}},{{y}_{2}} \right)=\left( a{{t}^{2}},2at \right)$.
The focus of the parabola is given as $\left( a.0 \right)$ .
Now, let us find the length of AB by using the distance formula,
i.e. distance $AB=\sqrt{{{\left( {{x}_{2}}-{{x}_{1}} \right)}^{2}}+{{\left( {{y}_{2}}-{{y}_{1}} \right)}^{2}}}=\sqrt{{{\left( a{{t}^{2}}-\dfrac{a}{{{t}^{2}}} \right)}^{2}}+{{\left( 2at+\dfrac{2a}{t} \right)}^{2}}}$
\[\begin{align}
& =\sqrt{{{a}^{2}}{{\left( {{t}^{2}}-\dfrac{1}{{{t}^{2}}} \right)}^{2}}+{{\left( 2a \right)}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}} \\
& \Rightarrow \sqrt{{{a}^{2}}{{\left( t-\dfrac{1}{t} \right)}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}+4{{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}} \\
\end{align}\]
We know that ${{a}^{2}}-{{b}^{2}}=\left( a+b \right)\left( a-b \right)$. Similarly, ${{\left( {{t}^{2}}-\dfrac{1}{{{t}^{2}}} \right)}^{2}}={{\left( t-\dfrac{1}{t} \right)}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}$
$\Rightarrow \left| \overline{AB} \right|=\sqrt{{{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}\left\{ {{\left( t-\dfrac{1}{t} \right)}^{2}}+4 \right\}}$ [taking ${{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}$common both the terms].
$=\sqrt{{{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}\left( {{t}^{2}}+\dfrac{1}{{{t}^{2}}}+2 \right)}=\sqrt{{{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{4}}}$ [we know ${{a}^{2}}+{{b}^{2}}+2ab={{\left( a+b \right)}^{2}}$]
Hence it become, $AB=a{{\left( t+\dfrac{1}{t} \right)}^{2}}$ ……………… (1)
Now, m = slope of line AB $=\dfrac{{{y}_{2}}-{{y}_{1}}}{{{x}_{2}}-{{x}_{1}}}=\dfrac{2at+\dfrac{2a}{t}}{a{{t}^{2}}-\dfrac{a}{{{t}^{2}}}}=\dfrac{2a\left( t+\dfrac{1}{t} \right)}{a\left( {{t}^{2}}-\dfrac{1}{{{t}^{2}}} \right)}=\dfrac{2\left( t+\dfrac{1}{t} \right)}{\left( t+\dfrac{1}{t} \right)\left( t-\dfrac{1}{t} \right)}=\dfrac{2}{t-\dfrac{1}{t}}$ .
So,
$\begin{align}
& m=\dfrac{2}{t-\dfrac{1}{t}} \\
& \Rightarrow \tan \alpha =m=\dfrac{2}{t-\dfrac{1}{t}} \\
& \Rightarrow t-\dfrac{1}{t}=\dfrac{2}{\tan \alpha }=2\cot \alpha \\
\end{align}$
We know that $\cot \theta =\dfrac{1}{\tan \theta }$ , by basic trigonometric identity.
Similarly
$\begin{align}
& {{\left( t+\dfrac{1}{t} \right)}^{2}}={{\left( t-\dfrac{1}{t} \right)}^{2}}+4 \\
& \Rightarrow {{\left( t+\dfrac{1}{t} \right)}^{2}}={{\left( 2\cot \alpha \right)}^{2}}+4=4{{\cot }^{2}}\alpha +4=4\left( {{\cot }^{2}}\alpha -1 \right) \\
\end{align}$
We know that ${{\cot }^{2}}\alpha -1=\cos e{{c}^{2}}\alpha $ .
$\therefore {{\left( t+\dfrac{1}{t} \right)}^{2}}=4\left[ {{\cot }^{2}}\alpha -1 \right]=4\cos e{{c}^{2}}\alpha $
We got the length of focal chord $AB=a{{\left( t+\dfrac{1}{t} \right)}^{2}}=4a\cos e{{c}^{2}}\alpha $
The equation of parabola given is \[{{y}^{2}}=8x\]. Now let us compare it with the general equation of the parabola is ${{y}^{2}}=4ax$ .
Hence, we get latus rectum $4a=8\Rightarrow a=2$ and $\alpha ={{60}^{\circ }}$
Thus, length focal chord $=4a\cos e{{c}^{2}}\alpha =4\times 2\cos e{{c}^{2}}{{60}^{\circ }}=8\cos e{{c}^{2}}{{60}^{\circ }}$
From trigonometric table we know that $\sin {{60}^{\circ }}=\dfrac{\sqrt{3}}{2}$
$\therefore \cos ec{{60}^{\circ }}=\dfrac{1}{\sin {{60}^{\circ }}}=\dfrac{2}{\sqrt{3}}$
$\therefore $ Length of focal chord $8\cos e{{c}^{2}}{{60}^{\circ }}=8\times {{\left( \dfrac{2}{\sqrt{3}} \right)}^{2}}=\dfrac{8\times 4}{3}=\dfrac{32}{3}$ .
Hence, it’s proved that both statement 1 and statement 2 are correct and R is the perfect reason for A.
Note: The angle inclination of a line is the angle formed by the intersection of the line and the x-axis, using a horizontal “run” of 1 and m for slope, The angle of inclination $\alpha ={{\tan }^{-1}}m$ or $m=\tan \alpha $. Thus, the reason why we took $\tan \alpha =slope$.
Complete step by step answer:
We have been given the equation of parabola as \[{{y}^{2}}=8x\] .
The length of the focal chord, ${{t}_{1}}{{t}_{2}}=-1$ i.e. ${{t}_{2}}=\dfrac{-1}{{{t}_{1}}}$ ,
Hence, if A and B are the coordinate of the point on the parabola then. We can take their coordinate as,
$A\left( at_{1}^{2},2a{{t}_{1}} \right)$ and $B\left( at_{2}^{2},2a{{t}_{2}} \right)$ .
But we found out that ${{t}_{2}}=\dfrac{-1}{{{t}_{1}}}$ .
$\therefore $ coordinate of B changes to, \[B\equiv \left( a{{\left( \dfrac{-1}{{{t}_{1}}} \right)}^{2}},2a\left( \dfrac{-1}{{{t}_{1}}} \right) \right)\equiv \left( \dfrac{a}{t_{1}^{2}},\dfrac{-2a}{{{t}_{1}}} \right)\].
Let’s assume ${{t}_{1}}=\dfrac{-1}{{{t}_{2}}}=t$.
Thus, we can write the coordinate as \[A\left( a{{t}^{2}},2at \right)\] and $B\left( \dfrac{a}{{{t}^{2}}},\dfrac{-2a}{t} \right)$ .
So, here $\left( {{x}_{1}},{{y}_{1}} \right)=\left( \dfrac{a}{{{t}^{2}}},\dfrac{-2a}{t} \right)$, $\left( {{x}_{2}},{{y}_{2}} \right)=\left( a{{t}^{2}},2at \right)$.
The focus of the parabola is given as $\left( a.0 \right)$ .
Now, let us find the length of AB by using the distance formula,
i.e. distance $AB=\sqrt{{{\left( {{x}_{2}}-{{x}_{1}} \right)}^{2}}+{{\left( {{y}_{2}}-{{y}_{1}} \right)}^{2}}}=\sqrt{{{\left( a{{t}^{2}}-\dfrac{a}{{{t}^{2}}} \right)}^{2}}+{{\left( 2at+\dfrac{2a}{t} \right)}^{2}}}$
\[\begin{align}
& =\sqrt{{{a}^{2}}{{\left( {{t}^{2}}-\dfrac{1}{{{t}^{2}}} \right)}^{2}}+{{\left( 2a \right)}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}} \\
& \Rightarrow \sqrt{{{a}^{2}}{{\left( t-\dfrac{1}{t} \right)}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}+4{{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}} \\
\end{align}\]
We know that ${{a}^{2}}-{{b}^{2}}=\left( a+b \right)\left( a-b \right)$. Similarly, ${{\left( {{t}^{2}}-\dfrac{1}{{{t}^{2}}} \right)}^{2}}={{\left( t-\dfrac{1}{t} \right)}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}$
$\Rightarrow \left| \overline{AB} \right|=\sqrt{{{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}\left\{ {{\left( t-\dfrac{1}{t} \right)}^{2}}+4 \right\}}$ [taking ${{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}$common both the terms].
$=\sqrt{{{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{2}}\left( {{t}^{2}}+\dfrac{1}{{{t}^{2}}}+2 \right)}=\sqrt{{{a}^{2}}{{\left( t+\dfrac{1}{t} \right)}^{4}}}$ [we know ${{a}^{2}}+{{b}^{2}}+2ab={{\left( a+b \right)}^{2}}$]
Hence it become, $AB=a{{\left( t+\dfrac{1}{t} \right)}^{2}}$ ……………… (1)
Now, m = slope of line AB $=\dfrac{{{y}_{2}}-{{y}_{1}}}{{{x}_{2}}-{{x}_{1}}}=\dfrac{2at+\dfrac{2a}{t}}{a{{t}^{2}}-\dfrac{a}{{{t}^{2}}}}=\dfrac{2a\left( t+\dfrac{1}{t} \right)}{a\left( {{t}^{2}}-\dfrac{1}{{{t}^{2}}} \right)}=\dfrac{2\left( t+\dfrac{1}{t} \right)}{\left( t+\dfrac{1}{t} \right)\left( t-\dfrac{1}{t} \right)}=\dfrac{2}{t-\dfrac{1}{t}}$ .
So,
$\begin{align}
& m=\dfrac{2}{t-\dfrac{1}{t}} \\
& \Rightarrow \tan \alpha =m=\dfrac{2}{t-\dfrac{1}{t}} \\
& \Rightarrow t-\dfrac{1}{t}=\dfrac{2}{\tan \alpha }=2\cot \alpha \\
\end{align}$
We know that $\cot \theta =\dfrac{1}{\tan \theta }$ , by basic trigonometric identity.
Similarly
$\begin{align}
& {{\left( t+\dfrac{1}{t} \right)}^{2}}={{\left( t-\dfrac{1}{t} \right)}^{2}}+4 \\
& \Rightarrow {{\left( t+\dfrac{1}{t} \right)}^{2}}={{\left( 2\cot \alpha \right)}^{2}}+4=4{{\cot }^{2}}\alpha +4=4\left( {{\cot }^{2}}\alpha -1 \right) \\
\end{align}$
We know that ${{\cot }^{2}}\alpha -1=\cos e{{c}^{2}}\alpha $ .
$\therefore {{\left( t+\dfrac{1}{t} \right)}^{2}}=4\left[ {{\cot }^{2}}\alpha -1 \right]=4\cos e{{c}^{2}}\alpha $
We got the length of focal chord $AB=a{{\left( t+\dfrac{1}{t} \right)}^{2}}=4a\cos e{{c}^{2}}\alpha $
The equation of parabola given is \[{{y}^{2}}=8x\]. Now let us compare it with the general equation of the parabola is ${{y}^{2}}=4ax$ .
Hence, we get latus rectum $4a=8\Rightarrow a=2$ and $\alpha ={{60}^{\circ }}$
Thus, length focal chord $=4a\cos e{{c}^{2}}\alpha =4\times 2\cos e{{c}^{2}}{{60}^{\circ }}=8\cos e{{c}^{2}}{{60}^{\circ }}$
From trigonometric table we know that $\sin {{60}^{\circ }}=\dfrac{\sqrt{3}}{2}$
$\therefore \cos ec{{60}^{\circ }}=\dfrac{1}{\sin {{60}^{\circ }}}=\dfrac{2}{\sqrt{3}}$
$\therefore $ Length of focal chord $8\cos e{{c}^{2}}{{60}^{\circ }}=8\times {{\left( \dfrac{2}{\sqrt{3}} \right)}^{2}}=\dfrac{8\times 4}{3}=\dfrac{32}{3}$ .
Hence, it’s proved that both statement 1 and statement 2 are correct and R is the perfect reason for A.
Note: The angle inclination of a line is the angle formed by the intersection of the line and the x-axis, using a horizontal “run” of 1 and m for slope, The angle of inclination $\alpha ={{\tan }^{-1}}m$ or $m=\tan \alpha $. Thus, the reason why we took $\tan \alpha =slope$.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Express the following as a fraction and simplify a class 7 maths CBSE
The length and width of a rectangle are in ratio of class 7 maths CBSE
The ratio of the income to the expenditure of a family class 7 maths CBSE
How do you write 025 million in scientific notatio class 7 maths CBSE
How do you convert 295 meters per second to kilometers class 7 maths CBSE
Trending doubts
10 examples of friction in our daily life
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Write down 5 differences between Ntype and Ptype s class 11 physics CBSE